Instalasi dan Implementasi Nutanix Foundation di PT. Tabel Data Informatika - Rahman Harist, Aulia; Putri, Hasanah (eProceedings of Applied Science, 2024)
This research focuses on the installation and implementation of Nutanix Foundation at PT Tabel Data Informatika, a leading company in the information technology industry. Nutanix Foundation is a hyperconverged platform that combines compute, storage and virtualization in one efficient solution. The research method included detailed installation steps, from environment preparation to final configuration, as well as integration with existing infrastructure, network setup, and system performance optimization. The implementation process also included training for the company's IT team to ensure a deep understanding of the new system. The implementation results showed increased operational efficiency, reduced maintenance costs, improved system reliability, and scalability of the IT infrastructure. Evaluation through trials and data analysis confirmed that Nutanix Foundation effectively meets the company's operational needs, providing a strong foundation for future IT infrastructure growth. These findings are important for other organizations considering the adoption of hyperconverged solutions, as Nutanix Foundation can optimize operational efficiency, reduce complexity, and increase IT infrastructure flexibility, supporting business growth and sustainability. Keywords - Nutanix Foundation, hyperconvergence, installation, operational efficiency, IT infrastructure, system integrationTranslated with DeepL.com (free version)